Mobile circular DNAs regulating memory and communication in CNS neurons - Smalheiser, Neil R. (Frontiers in Molecular Neuroscience, 2023)
Stimuli that stimulate neurons elicit transcription of immediate-early genes, a process which requires local sites of chromosomal DNA to form double-strand breaks (DSBs) generated by topoisomerase IIb within a few minutes, followed by repair within a few hours. Wakefulness, exploring a novel environment, and contextual fear conditioning also elicit turn-on of synaptic genes requiring DSBs and repair. It has been reported (in non-neuronal cells) that extrachromosomal circular DNA can form at DSBs as the sites are repaired. I propose that activated neurons may generate extrachromosomal circular DNAs during repair at DSB sites, thus creating long-lasting “markers” of that activity pattern which contain sequences from their sites of origin and which regulate long-term gene expression. Although the population of extrachromosomal DNAs is diverse and overall associated with pathology, a subclass of small circular DNAs (“microDNAs,” ∼100–400 bases long), largely derives from unique genomic sequences and has attractive features to act as stable, mobile circular DNAs to regulate gene expression in a sequence-specific manner. Circular DNAs can be templates for the transcription of RNAs, particularly small inhibitory siRNAs, circular RNAs and other non-coding RNAs that interact with microRNAs. These may regulate translation and transcription of other genes involved in synaptic plasticity, learning and memory. Another possible fate for mobile DNAs is to be inserted stably into chromosomes after new DSB sites are generated in response to subsequent activation events. Thus, the insertions of mobile DNAs into activity-induced genes may tend to inactivate them and aid in homeostatic regulation to avoid over-excitation, as well as providing a “counter” for a neuron’s activation history. Moreover, activated neurons release secretory exosomes that can be transferred to recipient cells to regulate their gene expression. Mobile DNAs may be packaged into exosomes, released in an activity-dependent manner, and transferred to recipient cells, where they may be templates for regulatory RNAs and possibly incorporated into chromosomes. Finally, aging and neurodegenerative diseases (including Alzheimer’s disease) are also associated with an increase in DSBs in neurons. It will become important in the future to assess how pathology-associated DSBs may relate to activity-induced mobile DNAs, and whether the latter may potentially contribute to pathogenesis.